The Impact of Anglicisms on Ukrainian Undergraduates as Consumers of Social Media Content - Yasser Al Tamimi; Yanina Lisun (Journal of Linguistics and Language Teaching)
This study investigates the use of English as a non-native language in communication and media consumption on social networks. It further examines the interaction between native and foreign languages within the linguistic environment of a Ukrainian academic institution. Additionally, it explores perceptions of English in media content creation and its role in modern marketing and public relations strategies employed by the institution through social networks. Based on descriptive analysis, using Google Analytics tools, of a survey of 385 Ukrainian university matriculated and prospective students, the study reveals a high diffusion rate of English as a foreign language and a relatively high level of proficiency, averaging between B1 and B2 (on the CEFR Global Scale) among 75% of the target audiences, which creates favourable conditions for English use in the processes of communication and creation of media content for the Ukrainian higher education institution. These results reveal the effectiveness of integrating the study of English as a non-native language into personal communications, media content creation, and communications of higher education institutions with students and applicants via social networks. The study suggests that higher education institutions should leverage the high level of English proficiency among students to enhance academic and media communication strategies. Furthermore, aligning institutional content with students' linguistic practices can strengthen engagement and improve overall communication effectiveness.